2021
DOI: 10.3390/ijms22031094
|View full text |Cite
|
Sign up to set email alerts
|

8q24.21 Locus: A Paradigm to Link Non-Coding RNAs, Genome Polymorphisms and Cancer

Abstract: The majority of the human genome is comprised of non-protein-coding genes, but the relevance of non-coding RNAs in complex diseases has yet to be fully elucidated. One class of non-coding RNAs is long non-coding RNAs or lncRNAs, many of which have been identified to play a range of roles in transcription and translation. While the clinical importance of the majority of lncRNAs have yet to be identified, it is puzzling that a large number of disease-associated genetic variations are seen in lncRNA genes. The 8q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 173 publications
0
12
0
Order By: Relevance
“…These cells could promote PCa progression by promoting immunosuppressive responses ( 48 , 49 ). Through CNV analysis, we found that 8q24.21, strongly associated with risk of tumors ( 50 , 51 ), was amplificated in subgroup 1. Some long non-coding RNAs, such as CCAT1 ( 52 , 53 ), PVT1 ( 54 ), PRNCR1 ( 55 ), and PCAT1 ( 56 ), in 8q24.21 have an influence in oncogenesis of PCa.…”
Section: Discussionmentioning
confidence: 92%
“…These cells could promote PCa progression by promoting immunosuppressive responses ( 48 , 49 ). Through CNV analysis, we found that 8q24.21, strongly associated with risk of tumors ( 50 , 51 ), was amplificated in subgroup 1. Some long non-coding RNAs, such as CCAT1 ( 52 , 53 ), PVT1 ( 54 ), PRNCR1 ( 55 ), and PCAT1 ( 56 ), in 8q24.21 have an influence in oncogenesis of PCa.…”
Section: Discussionmentioning
confidence: 92%
“…Significant non-coding RNAs such as PCAT1 which were found to be highly altered in chromosome 8 led us to believe that a high number of genes were altered in the chromosome 8 region (21) . It has been earlier reported in numerous articles about gains and losses in chromosome 8 (22,23) among various other cancers like breast, colorectal, and prostate cancer.…”
Section: Resultsmentioning
confidence: 80%
“…Cancer detection could benefit greatly from a better understanding of the co-expression network of lncRNAs and protein-coding genes. Cancer and other diseases can be caused by translocations and amplification of the 8q24 locus because it is susceptible to these events [30,31]. In addition, a number of critical regulatory elements can be found in this region, the absence of which can lead to the development of cancer.…”
Section: Discussionmentioning
confidence: 99%